Motivation and Characteristics of Poor Household on Selecting to Live at Sawahan Village, Sangkrah, Pasar Kliwon - Dahroni, Dahroni; Astuti, Wahyuni Apri; Sumardi, Sumardi (Forum Geografi, 2000)
This research tahes the title âmotivation and Characteristics of Poor Household That Choosing o Live in Kampung Saahan, Kelurahan Sangkrah, Kecamatan Pasar Kliwonâ. The research problem is, what is the motivation that encouraging resident aspirants who choosing Kampung Sawahan as their residences and the characteristics of poor households in terms of why do they choose Kampung Sawahan as tehir residences. The number of settlers population in Kampung Sawahan is 113 households. The research sampling was 100 household respondents. The research method used survey methods. Respondents were taken proportionally by random sampling from the population 113 households in Kampung Sawahan. Data analysis used frequency table analysis and cross table. The result of research showed that the encouraging motivation in choosing Kampung Saahan as their residences is, they feel the location is strategic enough, because it near trading centers where they work. Beside that there is s research result identifying the characteristic problems of poor households in terms of why do they chose to live in Kampung Sawahan, Kelurahan Sangkrah. The result is, their choices are based on assumptions that they can not buy a house because their poor incomes so that they rent a house from the owner.